Device Design for Multitask Graphene Electromagnetic Detection Based on Second Harmonic Generation - Yang, Cheng; Guo, Chu-Ming; Xu, Jie; Zhang, Hai-Feng (IEEE transactions on microwave theory and techniques, 2024)
The generation of a second harmonic wave (SHW) is a process of electromagnetic radiation at a specific frequency, often occurring in polarized ferroelectric crystals (FCs). In this article, a multitask graphene electromagnetic detection device (GEDD) based on second harmonic generation (SHG) is proposed. Through the periodic arrangement of different dielectric materials, the SHW conversion efficiency steadily increases within the structure, enabling multiscale detection of graphene thickness, angle, and hemoglobin concentration. By utilizing the shift f_{1} in the SHW peak (SHWP), the number of graphene layers (ranging from one to ten layers) can be accurately identified through thickness detection. The sensitivity ( S ) is 62.1 GHz/nm. Leveraging the high- S of 147 GHz/°, the shift f_{2} in the SHWP within the graphene structure can be employed for precise small-angle detection within a range of 4°-6°. Furthermore, by altering the filling medium of the test cavity, positioning the change value of SHWP can promote high-precision identification of hemoglobin concentrations of different blood types within the refractive index (RI) range of 1.6-1.7. The design of high- S multitask GEDD holds significant importance for expediting graphene material research. Moreover, it offers a novel approach for the precise application of SHW in the field of electromagnetic detection.